1993
DOI: 10.1099/0022-1317-74-5-937
|View full text |Cite
|
Sign up to set email alerts
|

Function of Rotavirus VP3 Polypeptide in Viral Morphogenesis

Abstract: The phenotype of the rotavirus SA-11 mutant tsB carrying a thermosensitive mutation in gene 3, which encodes VP3, was characterized further from both infected cells and purified viral particles. The mutant phenotype was initially identified as negative for in v&o double-and single-stranded RNA synthesis. Our results show that the in vitro transcriptional properties of the tsB mutant at the restrictive temperature were identical to those of the wild-type strain. Similar results were obtained with respect to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(15 reference statements)
2
11
0
Order By: Relevance
“…The observation that these types of particles can be formed when either VP1 or VP3 is knocked down suggests that their assembly can proceed in the absence of either protein. These results are in agreement with those reported by Vasquez et al (39). Taken together, these results suggest that the decrease in viral replication observed when VP3 was silenced is most probably due to an RNA replication defect rather than to an assembly problem, and they suggest that VP3 may have a novel and thus far undetermined role during in vivo replication of the virus.…”
supporting
confidence: 83%
See 3 more Smart Citations
“…The observation that these types of particles can be formed when either VP1 or VP3 is knocked down suggests that their assembly can proceed in the absence of either protein. These results are in agreement with those reported by Vasquez et al (39). Taken together, these results suggest that the decrease in viral replication observed when VP3 was silenced is most probably due to an RNA replication defect rather than to an assembly problem, and they suggest that VP3 may have a novel and thus far undetermined role during in vivo replication of the virus.…”
supporting
confidence: 83%
“…However, the newly synthesized dsRNA was not packaged, even when VP3 was added to the assay, so it was concluded that, in vivo, some other viral proteins, such as NSP2 and NSP5, should be needed for the encapsidation process and/or for the selection of the RNAs to be replicated. Using a temperature-sensitive virus with a lesion in VP3, Vásquez et al (39) demonstrated that this protein plays an important role during the RNA replication process since only empty, singleshelled particles were assembled at the nonpermissive temperature, suggesting that VP3 might have another function besides adding the cap structure to mRNAs. Additionally, Mansell and Patton (17) used a temperature-sensitive mutant with a lesion in VP6 to gain insight into the role of this protein in the replication of the virus.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, this enzyme does have an important role in genome replication in vivo, as small interfering RNA-mediated knockdown of VP3 expression in infected cells yields a reduction in progeny particles containing dsRNA (41,44). In contrast, both in vitro and in vivo experiments have shown that dsRNA synthesis by VP1 is strictly dependent upon the presence of the core shell protein VP2 (41,(45)(46)(47).…”
Section: Protein Requirements For Rv Rna Synthesismentioning
confidence: 99%